Distal Clavicle Insufficiency: Reconstruction With Iliac Crest Autograft of the Distal Clavicle and Acromioclavicular-Coracoclavicular Reconstruction - Mikalyn T. DeFoor, M.D.; Michael G. Rizzo, M.D.; Marco Adriani, M.D.; Ryan J. Whalen, B.S., C.S.C.S.; Samuel C. Hurley; Nate J. Dickinson, B.A.; CAPT. Matthew T. Provencher, M.D., M.B.A., MC, USNR (Ret.) (Arthroscopy Techniques)
Distal clavicle insufficiency, or a loss of the bony structure of the distal clavicle, generally after an injury or surgical procedure, may result in shoulder pain, dysfunction, scapular dyskinesia, and chronic acromioclavicular joint instability. If more than 15 to 20 mm of the distal clavicle is missing, chronic posterior instability of the distal clavicle may ensue and impinge on the deltotrapezial fascia and scapular spine. Although soft tissue reconstruction of the acromioclavicular-coracoclavicular (AC-CC) ligaments is a reliable procedure, if there is 15 to 20 mm or more of distal clavicle missing, it may be difficult to restore the mechanics of the scapular and glenohumeral joint. These can be seen after open or arthroscopic Mumford procedures (distal clavicle excision), AC-CC reconstructions with fracture, distal clavicle fractures, and other mechanisms. This technique article outlines an approach to distal clavicle insufficiency (>20 mm of missing distal clavicle bone) with iliac crest bone autograft reconstruction of the distal clavicle augmented with AC-CC soft tissue reconstruction.